NEUROPHYSIOLOGICAL BASIS IN CARDIAC NOCICEPTION-INDUCED REFLEXES FROM THE HEART: A COMPREHENSIVE REVIEW (Applied Biological Research, 2024)
The heart is considered an important reflexogenic organ and the stimulation of   cardiac nociceptors is responsible for the elicitation of different cardiogenic reflexes. Most likely this is the basic reason behind different clinical   presentations associated with heart failure, or myocardial infarction (MI).   Clinically, heart failure due to myocardial ischemia is associated with  bradycardia, hypotension, urge to pass urine, and stool. It is well established that   different chemical substances like lactic acid, prostaglandins, bradykinin, and   K+, are released during myocardial ischemia which, in turn, is responsible for the elicitation of cardiac pain that may result in different visceral and somatic   reflexes. So, understanding the basic physiological mechanism behind such   clinical association between cardiac ischemia-induced heart failure may help     clinicians manage this fatal condition. This paper presents a comprehensive   review on neurophysiological basis of different clinical presentations associated   with MI-induced heart failure. The review also analyses the neural pathway for   different cardiogenic reflexes which are associated with different clinical signs   or symptoms associated with cardiac failure and thereby may be responsible for   the diagnosis of early heart failure.
Keywords: Cardiogenic reflexes; cardiac nociceptors; cardiac ischemia; myocardial infarction-induced heart failure; neurophysiology of cardiac nociception